The impact of discharge readiness on post-traumatic growth in patients after thyroid cancer surgery: the mediating role of sickness-related stigma - Huang, Bin; Liu, Guangzhi; Huang, Jiaqian; He, Susu; Li, Wen; Xiao, Shanshan; Song, Xiaohua; Chen, Hongtao (Frontiers in oncology, 2024)
To investigate the relationship between post-traumatic growth, morbidity stigma and readiness for discharge in post-operative thyroid cancer patients. 422 post-operative thyroid cancer patients from three tertiary care hospitals in Hunan and Tianjin were surveyed using the General Information Questionnaire, the Post-traumatic Growth Scale, the Readiness for Discharge Scale, and the Social Influence Scale. Discharge readiness positively predicted the level of post-traumatic growth in thyroid cancer patients (P < 0.01), and morbidity stigma negatively predicted post-traumatic growth (P < 0.01), with morbidity stigma playing a mediated role between discharge readiness and post-traumatic growth. Readiness for discharge can positively predict post-traumatic growth, and morbidity stigma plays a mediating role between readiness for discharge and post-traumatic growth. It is suggested that clinical and nursing staff should strengthen patients' discharge readiness guidance and education, help patients and their families establish an effective feedback mechanism for disease condition and psychological cognitive condition, focus on reducing patients' sense of shame, and improve patients' physical and mental health.